Pengaruh Pemberian Buah Kurma Terhadap Kelancaran Produksi Asi Ibu Nifas Di PMB Hernita, AMD.KEB Bandar Lampung - Ananda Primata Beuty; Enny Yuliaswati (Jurnal Anestesi, 2023)
Background: The coverage of infants receiving exclusive breastfeeding in Lampung Province in 2020 is 70.1%, which is still below the expected target of 80%. One of the foods that can facilitate the production of breast milk is dates, dates contain galactogogues which are capable of inducing lactation with dopamine pressure, resulting in an increase in prolactin production. Dates contain a hormone similar to the hormone oxytocin, which is a hormone produced by the neurohypophysia so that it stimulates the mammary glands to produce breast milk. Objective: To determine the effect of giving dates on the smooth production of breast milk in postpartum mothers. Methods: This type of research is a Quasy Experiment Design with a Non Equivalent Control Group Design study with a sample of 40 subjects. The instruments used in this study were SOP sheets for giving dates and observation sheets for signs of assessing the smoothness of breastfeeding. The intervention of giving dates was given 7 eggs per day which were consumed for 4 days. Results: All respondents before being given treatment experienced breastfeeding difficulties as many as 20 respondents (100%) and after being given the date palm treatment the respondents were in the smooth category as many as 18 respondents (90%). Conclusion: There is an Effect of Giving Dates on the Smooth Production of Breast Milk for Postpartum Mothers.